Evaluating the quality of life in asthmatic children less than 5 years in an urban setting in Mumbai: A pilot study - Pherwani, Asha (Indian Journal of Child Health, 2015)
Introduction: Quality of life questionnaires (QOLQs) are an important part of the clinical assessment. There are few studies in India evaluating QOL in children with childhood asthma. Objectives: The objective was to construct a parent answered QOLQ for asthmatic children under 5 years of age and to compare QOLQ with symptoms. Materials and Methods: Exploratory/pilot study conducted between January and December 2011 in asthma clinic of an urban teaching hospital. Asthmatic children below 5 years of age, who had at least three asthma attacks in the past year, were included in the study. A QOLQ was constructed having 18 items,distributed under four domains (symptoms, environment, physical activity, and behavior). Validity of QOLQ was checked and was presented to parents in a simple language, and they were taught to score them from 1 to 7. Results: Study consists of 41 asthmatic children (mean age = 3.7±1.1 years) with 26 (63.8%) male and 15 (36.5%) females. 15 age-matched (mean age 4±1.2 years) normal controls were also taken. The mean score was significantly higher (p?0.05) for the domain of symptoms (4.2±2), than the domains of environment (3.6±1.8), and behavior (3.6±1.6), and these were higher than those of physical activity (3.2±2.65, p?0.05). The meandomains of asthmatics were significantly higher (30-34%) than the controls, suggesting that the QOLQ was measuring what it was supposed to measure. Scores of the QOLQ correlated with the severity of symptoms. Conclusion: It is possible to determine the QOL of children below 5 years of age with parents acting as a proxy. However, larger data is needed to confirm its clinical usefulness and application.